KEEFEKTIFAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTU MEDIA AUDIO VISUAL DAN BENDA KONKRET TERHADAP HASIL BELAJAR SISWA TEMA 6 PANAS DAN PERPINDAHANNYA SUBTEMA 3 PENGARUH KALOR TERHADAP KEHIDUPAN UNTUK SISWA KELAS 5 SDN 6 BANGSRI - Febriana Cicilia; Fine Reffiane; Eka Sari Setianingsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The background that drives this research is the low student learning outcomes. This is because teachers still use conventional methods such as lectures and in learning rarely use media, this causes students to be less active in participating in learning. The purpose of this study was to determine the effectiveness of the Problem Based Learning (PBL) Model Aided by Audio Visual Media and Concrete Objects on Student Learning Outcomes Theme 6 Heat and its Transfer Subtheme 3 Effect of Heat on Life for Grade 5 Students at SDN 6 Bangsri. This type of research is quantitative research in the form of Pre-Experimental Designs with One-Group Pretest-Posttest Design. The samples taken were 28 fifth grade students of SDN 6 Bangsri using the Nonprobability Sampling technique. The data in this study were obtained through tests, observations, interviews and documentation. The results of the study after receiving treatment showed an increase in student learning outcomes which can be seen from the results of the pretest and posttest. The pretest was 57,14286 and the posttest average value was 78,85714. The initial learning mastery was 25% to 91%, so the learning mastery increased. This is evidenced by the obtained tcount of Pretest equal to, tcount = 7.5474 and to find out ttable with a significant t value of 5% obtained ttable of 1.701. So the value of tcount > ttable which means H0 is rejected and Ha is accepted.